Efficacy and safety of long-term thiopurine maintenance treatment for ulcerative colitis in Turkey: A single-center experience - Özgenç, Funda; Karakoyun, Miray; Ecevit, Çiğdem; Hekimci, Hamiyet; Kıran Taşçı, Ezgi; Erdemir, Gülin (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Thiopurines are widely used in the treatment of inflammatory bowel disease, but data are limited. Or aim was to determine the outcome of thiopurine application in children diagnosed with ulcerative colitis (UC). Materials and Methods: Forty-eight patients with UC, diagnosed at our center between 2005 and 2016 and applied azathiopurine (AZA), were included in the study. Data were collected retrospectively. The diagnosis of UC was based on the conventional clinical, radiological, histological, and endoscopic assessment. All patients with UC at this intercept were analyzed at the 4- and 6-week and 3-month intervals after remission to determine patient characteristics, thiopurine properties, and its efficacy and toxicity. Determination of remission, relapse, and steroid refractoriness/dependency were guided according to the European Crohn’s and Colitis Organisation consensus. Results: Azathiopurine was started at the median 1 month (0-12 months), and it was applied thereafter for maintenance (n=43). Response to remission induction was obtained in 40 (93.7%) patients. The median duration of the AZA treatment was 24 months (5-63). In 34 (85%) of the 40 children, it was well tolerated until the last visit. During the follow-up, adverse events occurred in 6 patients. These are leucopenia, neutropenia, vomiting, diarrhea, and skin rush. Conclusion: Thiopurine is an appropriate treatment option for remission in patients with UC. For a long-term follow-up, it is very important to identify patients with UC who have clinical remission with side effects and with thiopurine application. Cite this article as: Özgenç F, Karakoyun M, Ecevit Ç, Hekimci H, Kıran Taşçı E, Erdemir G. Efficacy and safety of long-term thiopurine maintenance treatment for ulcerative colitis in Turkey: A single-center experience. Turk J Gastroenterol 2018; 29: 650-4.